PENGEMBANGAN LEMBAR KERJA PESERTA DIDIK (LKPD) BERBASIS MODEL DISCOVERY LEARNING PADA MATERI ASAM BASA DI SMA NEGERI 1 SIOMPU BARAT - Haetami, Aceng; Astuti, Niang Sri; Maysara (Lembaga Pengembangan Kinerja Dosen, 2022)
This study aims to: determine the quality and readability of acid-base worksheets based on discovery learning. The research method used is R&D (Research and Development) with research stages adapted to the Borg and Gall theory modified by Sugiyono. The research stages carried out were data collection, product design, design validation, design revision, limited trial, and product revision. The quality of the worksheet student developed was validated by 3 material experts. The readability test of the LKPD developed was seen from the responses of 9 students. The results showed that the average validator assessment was 92.11% (very valid category). The average assessment of the readability test by students is 3.46 with a good category (limited scale trial). Based on the validation of experts and student responses, the LKPD developed was valid and suitable to be used as a learning tool in acids and bases